2022
DOI: 10.3390/microorganisms10020312
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Diseases from the Microbiome Perspective: How Microorganisms Could Change the Approach to Benign and Malignant Diseases

Abstract: Recent evidence regarding microbiota is modifying the cornerstones on pathogenesis and the approaches to several gastrointestinal diseases, including biliary diseases. The burden of biliary diseases, indeed, is progressively increasing, considering that gallstone disease affects up to 20% of the European population. At the same time, neoplasms of the biliary system have an increasing incidence and poor prognosis. Framing the specific state of biliary eubiosis or dysbiosis is made difficult by the use of hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 138 publications
(183 reference statements)
2
16
0
1
Order By: Relevance
“…The term “microbiota” identifies the symbiotic relationship of living microorganisms (Bacteria, Fungi, and Viruses) present in our body, defined by not only the community of the microorganisms but also their “theatre of activity” [ 1 , 2 ]. In fact, the microbiota interacts with several human organs, and its bacterial composition shows tissue-specific differences and influences the host health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term “microbiota” identifies the symbiotic relationship of living microorganisms (Bacteria, Fungi, and Viruses) present in our body, defined by not only the community of the microorganisms but also their “theatre of activity” [ 1 , 2 ]. In fact, the microbiota interacts with several human organs, and its bacterial composition shows tissue-specific differences and influences the host health.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the F/B ratio is > 0.8 and it correlates with the status of saccharolytic fermentation. It has been confirmed that several species belonging to the Firmicutes Phylum have a higher and better degradation capacity of complex sugars and fatty acids; therefore, their increase contributes to the development of obesity [ 2 , 3 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, significant overgrowths of Streptococcus and Alistipes have been reported in GB stone patients, and both are known to have pro-inflammatory effects and promote gut barrier dysfunction [ 26 , 27 ]. While the precise mechanisms underlying the relationship between gut microbiome and GB stone are still not fully understood, it is clear that the gut microbiome is an important factor to consider in the pathology of GB stones [ 28 , 29 , 30 ]. In addition to the changes in overall gut microbiota composition, specific gut microbiota lineages have also been implicated in the development and progression of gallstone diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that dysbiosis or an imbalance of gut microbiota may lead to the release of inflammatory and vasoactive substances as well as changes in bile acid metabolism and host metabolic pathways. These changes may also contribute to the promotion of chronic pro-inflammatory states, as well as the disruption of intestinal permeability [ 28 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this normal biliary microbiome mainly included Firmicutes, Actinobacteria, Proteobacteria, and Bacteroidetes which were also found in the human gut [70,71]. This can partly be explained by the close association of the human gut and the biliary tract and the involvement of enteric bacteria in enterohepatic circulation but the evidence is largely limited to animal models and an ideal human experimental model is required [72].…”
Section: The Biliary Microbiomementioning
confidence: 99%